Pregnancy related complications in women with hypertrophic cardiomyopathy. Issue 7 (1st July 2003) - Thaman, R; Varnava, A; Hamid, M S; Firoozi, S; Sachdev, B; Condon, M; Gimeno, J R; Murphy, R; Elliott, P M; McKenna, W J
Abstract : Objectives: To determine whether pregnancy is well tolerated in hypertrophic cardiomyopathy. Setting: Referral clinic. Design: The study cohort comprised 127 consecutively referred women with hypertrophic cardiomyopathy. Forty (31.5%) underwent clinical evaluation before pregnancy. The remaining 87 (68.5%) were referred after their first pregnancy. All underwent history, examination, electrocardiography, and echocardiography. Pregnancy related symptoms and complications were determined by questionnaire and review of medical and obstetric records where available. Results: There were 271 pregnancies in total. Thirty six (28.3%) women reported cardiac symptoms in pregnancy. Over 90% of these women had been symptomatic before pregnancy. Symptoms deteriorated during pregnancy in fewer than 10%. Of the 36 women with symptoms during pregnancy, 30 had further pregnancies. Symptoms reoccurred in 18 (60%); symptomatic deterioration was not reported. Heart failure occurred postnatally in two women (1.6%). No complications were reported in 19 (15%) women who underwent general anaesthesia and in 22 (17.4%) women who received epidural anaesthesia, three of whom had a significant left ventricular outflow tract gradient at diagnosis after pregnancy. Three unexplained intrauterine deaths occurred in women taking cardiac medication throughout pregnancy. No echocardiographic or clinical feature was a useful indicator of pregnancy related complications. Conclusions: Most women with hypertrophic cardiomyopathy tolerate pregnancy well. However, rare complications can occur and therefore planned delivery and fetal monitoring are still required for some patients.